Fertility in Bitches following Intravaginal Artificial Insemination using fresh semen - SATHIAMOORTHY, T; ASOKAN, S A; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2023)
Twenty four bitches of different breeds were divided into group I and II, they· were bred by artificial inseminatioo and natural service, respectively. Ferti_le breeding time was assessed by vaiinal cytology and vaginoscopy. Breeding with fresh ·semen was done when the vaginal smears showed 70 80 per cent of superficial and comified cells and observation of vaginal mucosa! crenulation through vaginoscope. The breeding continued at every 3"’ day until diestrus. Semen was collected from six male dogs ofrespettive breeds by digital manipulation. Conception rate of66.66 and 6 ’. l 5 per cent and litter size of 5.8 ± 0.46 and 4.6 :d: 0.32 was obtained in group 1 and group II respectively in this study.